MAXIMIZATION INCOME OF FISHERMEN PANCING ULUR IN THE VILAGE TETE B TOJO UNA-UNA - Dafina Howara (Tadulako University, 2015)
Beliefs about profitability of different locations and the decision of how long to fish in a particular location are likely to affect the variability of fishermen’s incomes. This paper examine the Maximization of income of the fishermen fishing In the village of Tete B TojoUna-Una. Data analysis using LINDO analysis.The population in this research are 54 house hold from fisherman pancingulur. Respondent performed by using simple random sampling method, therefore the number of samples in the study are 37 families. The analysis showed that the maximum income of fishermen fishing in the villageTete B is Rp 40.036.480,00 with the total production of 15.667 kg produced for one month period of catching. Resources used to obtain the maximum income is 4.856,67 liters of gasoline, lubricants or oils 47 liters, ice is 3.446.67packs, consumption is Rp 6.000.333,33 and cigarette is 1.096,67 wrap.